Development of UV-Chemometric techniques for resolving the overlapped spectra of aspirin, caffeine and orphenadrine citrate in their combined pharmaceutical dosage form - Sobhy M. El-Adl; Amr A. Mattar; Omar M. El-Abassy; Mahmoud M. Sebaiy (BMC Chemistry)
Abstract A UV-chemometric approach has been developed to analyze a ternary combination of aspirin, caffeine, and orphenadrine citrate without the need for previous separation. The method is easy, specific, accurate, and highly precise. The three medications were evaluated simultaneously utilizing CLS, PLS, and PCR, which were generated based on separate data sets that yielded superior findings. Regrettably, their accurate estimation could only be achieved using the PLS approach. In order to determine the prediction power of each chemometric approach, its validity has been tested using 8 synthetic mixes. The latent variable number varies across various models as the dataset changes. The comparison of various methodologies and the assessment of the predictive capacity of each set of data were done using the predicted residual error sum of squares (PRESS) and the root mean square error of prediction (RMSEP). The created approach was also used to statistically compare the performance of PLS in a dataset with zero absorption, as well as to compare the performance of the offered chemometric methods in various datasets. The environmental impact of the created approach was assessed to determine the overall ecological sustainability of the designed methodology. According to the new Blue Applicability Grade Index (BAGI) evaluation methodology, the suggested technique was also found to be practicable.